Acute phase response of sole ulcer, white line disease and digital dermatitis in dairy cows. (September 2022) - Pirkkalainen, Hertta; Talvio, Isto; Kujala-Wirth, Minna; Soveri, Timo; Orro, Toomas
Highlights: Serum amyloid A, a marker of inflammation, was still elevated two weeks after treatment of sole ulcers. Body temperature and concentration of cytokine interleukin-6 declined from day 0 to day 7 in sole ulcer group. Sole ulcer is a chronic hoof disorder that heals slowly and therefore early detection, good management, and proper pain medication of cows with sole ulcers is important. Abstract: Hoof disorders cause lameness and welfare problems for dairy cattle. Acute phase proteins, including serum amyloid A and haptoglobin, with increased rectal temperature and interleukin-6 concentrations, are markers of acute phase response. This study assessed the inflammatory response of cows with either sole ulcer, white line disease or digital dermatitis compared to healthy cows. Another aim was to monitor the inflammatory response changes over time after diagnosis (at hoof trimming, seven and 14 days later) in cows with different hoof disorders. Serum amyloid A concentration in cows with sole ulcer was significantly higher compared with the control group (cows with no hoof lesions) within the two-week study period. Interleukin-6 and rectal temperature declined from day zero to day seven in the sole ulcer group. These results suggest that sole ulcers initiate a long lasting systemic inflammatory response in dairy cows.